Culture of Communication of Slovak Politicians - Rysová, Andrea (Political Preferences, 2021)
The term political culture involves a wide range of contexts and evokes a different spectrum of ideas, opinions, and definitions. Nowadays, perhaps slightly more than ever, we encounter views and statements that refer to the low level of political culture in our country. Many times, these are declarations that apply not only to specific political parties or politicians, but also to citizens, or even to the entire nation, which is (often by itself) described as having no political culture. And this notion, unfortunately, also harmfully affects the formation of our national identity as such; how we perceive ourselves, what patterns we adopt, and what standards we accept. In our paper, we focus on the culture of the Slovak political communication, while paying special attention to the linguistic utterances of selected representatives of the Slovak political scene. In this context, the language will act as a tool for communication between political representatives themselves, between political officials and citizens, but also as a tool of discussion on politics among people.